2021
DOI: 10.1108/ilt-06-2021-0196
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of ball screw feed system with abrupt-change-nonlinear drive stiffness

Abstract: Purpose For ball screw feed system, a sudden start or stop has a great influence on the transmission stiffness, so the axial stiffness mutation of feed system will occur. The purpose of this paper is to study the influence of acceleration on the transmission stiffness and dynamic characteristics of the ball screw feed system. Design/methodology/approach Taking the ball screw feed system as a research object, on the basis of the Hertz contact theory and the mixed element method, axial stiffness model and dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Gao et al. [141] found out how load, nut contact stiffness, bearing contact stiffness and preload would affect the ball screw pair's transmission stiffness. Liu et al.…”
Section: Problems Of Existing Research and Potential Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gao et al. [141] found out how load, nut contact stiffness, bearing contact stiffness and preload would affect the ball screw pair's transmission stiffness. Liu et al.…”
Section: Problems Of Existing Research and Potential Solutionsmentioning
confidence: 99%
“…Xu et al [140] provided the corresponding relationship between the axial force applied on the nut of a ball screw pair and the axial displacement of the nut, with consideration of the preload. Gao et al [141] found out how load, nut contact stiffness, bearing contact stiffness and preload would affect the ball screw pair's transmission stiffness. Liu et al [142] established a nine degrees-of-freedom dynamic model to study the relationship of contact deformation and restoring force of each ball in the ball screw pair.…”
Section: Insufficient Maturity Of Research On Ema Dynamic Modellingmentioning
confidence: 99%